Executive Committee Minutes 2020-04-09 - Academic Senate:::::::::
Approval of Agenda – amended and approved. Minutes of 3/26/2020 – Approved. Chair Report. President Report. Vice President of Administration and Finance Report. Provost Report. Vice Chair Report. Associated Students Report. From University Standards and EPC: Revision to Withdrawal Policy – approved for Senate agenda. From FSAC: Statement about Teaching Sensitive Materials – referred back to committee. Temporary Modifications to University Policies 1987-4, Credit/No Credit Policy, 2009-5 Withdrawal from Courses, 2009-4 Academic Probation, Disqualification, and Progress, Due to Special Circumstances of the COVID-19 Pandemic – approved as an information item to Senate. GIG presentation scheduled for April 30th. Vice President for Student Affairs Report. EPC Report. FSAC Report. Senate Agenda approved.